Book Review: Teologi Multikultural - Nelly (Sekolah Tinggi Teologi Baptis Indonesia, 2020)
Multicultural theology is a theology that is built from a wealth of cultural background and contextualization of wealth for people's way of life. Thus, this theology is broad in the horizon but narrow in implementation because it is very dependent on the context in which it is located. This book explains five important aspects of building a multicultural theology namely relational, social, operational, moral, and transformational. The main problem in this theology is its position which is at odds with the understanding of pluralism, does not stand on inclusivism and exclusivity, and has a theological path that is not the same as contextualization.